The Samaritan Version of the Book of Numbers with Hebrew Variants A Close Textual Study. - Phillips, David Lee. (Lewiston : The Edwin Mellen Press, 2014)
The voice of long-dead native speakers is resurrected in this outstanding study on the Old Testament Book of Numbers. Accurate translation of Old Testament scripture has always been problematic without the input of native speakers for the written languages of that record. This work seeks to stay as close as possible to the voice of the verbs and non-verbs of the Hebrew sentences of those ancient texts.
21,21a SIYYON the Amorite, the King of Heshbon21,21b The sons of Esau who live on Sha'er.; 21, 23b Begin the conquest of his land!; 27,23b Yahweh your God will protect you; 31,21a Moses said to Elaazar the priest; Appendices of Variant Words; Appendix L -- Samaritan Hebrew Attested in Greek; Appendix M -- Samaritan Hebrew Attested in MT Manuscripts; Appendix U -- Unattested Variants; Chronology; Bibliography; Index
Description based upon print version of record.
Description based on print version record.
Keywords: Bible. -- Criticism, Textual; Bible. -- Versions -- Samaritan; Paleography, Hebrew; RELIGION / Biblical Studies / Old Testament; Electronic books